Endothelial GNAQ p.R183Q Increases ANGPT2 (Angiopoietin-2) and Drives Formation of Enlarged Blood Vessels. Issue 1 (January 2022) - Huang, Lan; Bichsel, Colette; Norris, Alexis L.; Thorpe, Jeremy; Pevsner, Jonathan; Alexandrescu, Sanda; Pinto, Anna; Zurakowski, David; Kleiman, Robin J.; Sahin, Mustafa; Greene, Arin K.; Bischoff, Joyce
Abstract : Objective: Capillary malformation (CM) occurs sporadically and is associated with Sturge-Weber syndrome. The somatic mosaic mutation in GNAQ (c.548G>A, p.R183Q) is enriched in endothelial cells (ECs) in skin CM and Sturge-Weber syndrome brain CM. Our goal was to investigate how the mutant Gαq (G-protein αq subunit) alters EC signaling and disrupts capillary morphogenesis. Approach and Results: We used lentiviral constructs to express p.R183Q or wild-type GNAQ in normal human endothelial colony forming cells (EC-R183Q and EC-WT, respectively). EC-R183Q constitutively activated PLC (phospholipase C) β3, a downstream effector of Gαq. Activated PLCβ3 was also detected in human CM tissue sections. Bulk RNA sequencing analyses of mutant versus wild-type EC indicated constitutive activation of PKC (protein kinase C), NF-κB (nuclear factor kappa B) and calcineurin signaling in EC-R183Q. Increased expression of downstream targets in these pathways, ANGPT2 (angiopoietin-2) and DSCR (Down syndrome critical region protein) 1.4 were confirmed by quantitative PCR and immunostaining of human CM tissue sections. The Gαq inhibitor YM-254890 as well as siRNA targeted to PLCβ3 reduced mRNA expression levels of these targets in EC-R183Q while the pan-PKC inhibitor AEB071 reduced ANGPT2 but not DSCR1.4. EC-R183Q formed enlarged blood vessels in mice, reminiscent of those found in human CM. shRNA knockdown of ANGPT2 in EC-R183Q normalized the enlarged vessels to sizes comparable those formed by EC-WT. Conclusions: Gαq-R183Q, when expressed in ECs, establishes constitutively active PLCβ3 signaling that leads to increased ANGPT2 and a proangiogenic, proinflammatory phenotype. EC-R183Q are sufficient to form enlarged CM-like vessels in mice, and suppression of ANGPT2 prevents the enlargement. Our study provides the first evidence that endothelial Gαq-R183Q is causative for CM and identifies ANGPT2 as a contributor to CM vascular phenotype. Abstract : Supplemental Digital Content is available in the text.